Literasi Digital sebagai Strategi Branding pada UMKM Lele Bumbu - Eka Merdekawati Imelda Seseli; Melvin Krisdiana Djami Rane; Dian Nustanti Ndaomanu; Donny Mercys Bessie; Mesri Wehelmina Nisriani Manafe (LP2M INSURI Ponorogo, 2025)
As the province's capital, Kupang City has adequate communication and internet infrastructure, with an internet penetration rate above 70%. However, not all MSME (Micro, Small, and Medium Enterprise) actors have optimally utilized these facilities to advance their businesses. Lele Bumbu is one such MSME that remains stagnant, even though catfish consumption in Indonesia remains one of the main protein sources with consistently high demand. Due to limited capital and low digital literacy, Lele Bumbu operates as a home-based industry and has not utilized digital marketing effectively. This community service program (PkM) aims to assist and train Lele Bumbu to improve product quality, establish proper management, and adopt digital marketing and financial technology, ultimately creating a strong digital brand. The method employed uses a PRA (Participatory Rural Appraisal) approach through collecting primary and secondary data, focus group discussions (FGD), and implementation via socialization, training, and mentoring for business owners. The PkM activities increased business owners' capacity to master digital marketing, financial recording applications, and business management. Based on the analysis, business management capacity improved by more than 70%, the ability to use marketing and financial applications increased by more than 75%, and product quality improved by 50% regarding the product and its packaging.